2018
DOI: 10.1101/189811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-stage processing of category and variation information by entangled interactive mechanisms of peri-occipital and peri-frontal cortices

Abstract: Abstract-Invariant object recognition, which refers to the ability of precisely and rapidly recognizing objects in the presence of variations, has been a central question in human vision research. The general consensus is that the ventral and dorsal visual streams are the major processing pathways which undertake category and variation encoding in entangled layers. This overlooks the mounting evidence which support the role of peri-frontal areas in category encoding. These recent studies, however, have left op… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…Our findings support theories suggesting that fronto-occipital information transfer may feedback (pre-existing) face templates, against which the input faces are compared for correct recognition (Bar et al, 2006;Summerfield et al, 2006). As an advantage to the previous results, which could not determine the content of the transferred signals (Bar et al, 2006;Summerfield et al, 2006;Goddard et al, 2016;Karimi-Rouzbahani et al, 2018;Karimi-Rouzbahani et al, 2019), using our novel connectivity analyses, we showed that the transferred signal contained information which contributed to the categorization of familiar and unfamiliar faces.…”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…Our findings support theories suggesting that fronto-occipital information transfer may feedback (pre-existing) face templates, against which the input faces are compared for correct recognition (Bar et al, 2006;Summerfield et al, 2006). As an advantage to the previous results, which could not determine the content of the transferred signals (Bar et al, 2006;Summerfield et al, 2006;Goddard et al, 2016;Karimi-Rouzbahani et al, 2018;Karimi-Rouzbahani et al, 2019), using our novel connectivity analyses, we showed that the transferred signal contained information which contributed to the categorization of familiar and unfamiliar faces.…”
Section: Discussioncontrasting
confidence: 45%
“…The RSA-based connectivity method used in this study further develops a recent shift towards multivariate brain connectivity methods (Anzellotti and Coutanche, 2018;Basti et al, 2020;Keitzmann et al, 2019;Goddard et al, 2016;Clarke et al, 2018;Karimi-Rouzbahani, 2018;Karimi-Rouzbahani et al, 2019;Karimi-Rouzbahani et al, 2020), and introduces several advantages over previous methods of connectivity analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations